Morphological Biomarkers Related to Visual Acuity in Patients With Radiation Retinopathy Treated With Intravitreal Ranibizumab - Corona, Stephanie Trejo (Ophthalmic surgery, lasers & imaging retina, 2024)
BACKGROUND AND OBJECTIVE: Our objective was to monitor variables via spectral-domain optical coherence tomography (SD-OCT) and identify the most relevant biomarkers related to best-corrected visual acuity (BCVA) in radiation retinopathy (RR)